Delayed Gadolinium Leakage in Ocular Structures: A Potential Marker for Age- and Vascular Risk Factor‐Related Small Vessel Disease?. Issue 7 (July 2021) - Galmiche, Chloé; Moal, Bertrand; Marnat, Gaultier; Sagnier, Sharmila; Schweitzer, Cédric; Dousset, Vincent; Sibon, Igor; Tourdias, Thomas
Abstract : Background: Gadolinium leakage in ocular structures (GLOS) was recently observed in fluid-attenuated inversion recovery (FLAIR) images obtained the day after an initial gadolinium injection in stroke patients. The specificity of GLOS to stroke and its mechanisms remain unclear. Objective: We investigated the factors associated with GLOS in a cohort of patients presenting with acute neurological deficits. Materials and Methods: This retrospective study included consecutive patients admitted to our stroke unit for acute neurological deficit between July 2017 and August 2018 who underwent baseline brain magnetic resonance imaging with the injection of a macrocyclic gadolinium agent and another scan without injection within 72 hours. The patients were separated into a stroke group and a stroke mimic group based on diffusion-weighted images. Gadolinium leakage in ocular structures was defined as a bright signal in the vitreous in follow-up FLAIR compared with baseline FLAIR (pregadolinium). Clinical data were collected together with imaging features from the baseline scans, including the volume of the infarct and of hypoperfusion if applicable, white matter hyperintensities, the number of lacunes, and the number of microbleeds, which were combined to yield a small vessel disease (SVD) score. We compared the prevalence of GLOS in both groups using the χ 2 test. In the entire cohort, univariate and multivariate regression models were used to test the associations between GLOS and the collected data. Results: Among the 467 patients included in the study, GLOS was observed in similar proportions in the stroke group (32.2%, 136/422) and the stroke mimic group (28.9%, 13/45; mean difference, 3.3%; 95% confidence interval, −10.9 to 17.6; P = 0.65). In univariate analysis, GLOS was associated with older age, increased prevalence of vascular risk factors, brain imaging features of SVD (white matter hyperintensities, lacunes, microbleeds), as well as with impairment of renal function and increased dose of gadolinium. No associations were found with factors related to stroke, such as its volume, acute treatment, or rate of recanalization. Multivariate analyses showed that aging ( P < 0.001), diabetes ( P = 0.010), severe renal failure ( P = 0.004), and increased dose of gadolinium ( P < 0.001) were independent contributors to GLOS. Conclusions: Gadolinium leakage in ocular structures, which occurs more commonly at higher concentrations of gadolinium, is not specific to stroke and may represent increased permeability of the blood-retinal barrier associated with age- and vascular risk factor‐related SVD. Abstract : Supplemental digital content is available in the text.